The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4103/0257-7941.157146
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective activity of Bilvādi agada in gentamicin induced nephrotoxicity in male Wistar rats

Abstract: Background:Gentamicin (GM) nephrotoxicity accounts for 10–30% of the acute renal failure (ARF) among drug-induced ARF. In Ayurveda such side effects are considered as the poisonous effects of low potent poisons called gara viṣa. Bilvādi agada (BA), a classical formulation is indicated in gara viṣa and most of its ingredients have proven for their nephroprotective activity.Aim:The aim was to evaluate the effect of BA in GM-induced nephrotoxicity in male Wistar rats.Materials and Methods:BA, GM, normal saline we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
1
12
0
3
Order By: Relevance
“…Many plants have been used for the treatment of kidney failure in traditional system of medicine throughout the world (Kumar et al, 2013). Many research studies reported the protective effect of plant extracts on gentamicin induced nephrotoxocity, which supports our current studies (Kanna et al, 2015;Manimala et al, 2015;Padmalochana and Rajan, 2015;Shalaby and Hammouda, 2014;Tavafi et al, 2012). Tecoma stans leaves, bark and roots contain many biologically active chemicals and extracts from those tissues have been used in traditional folk medicine to treat many diseases and conditions (Liogier, 1990).…”
Section: Introductionsupporting
confidence: 80%
“…Many plants have been used for the treatment of kidney failure in traditional system of medicine throughout the world (Kumar et al, 2013). Many research studies reported the protective effect of plant extracts on gentamicin induced nephrotoxocity, which supports our current studies (Kanna et al, 2015;Manimala et al, 2015;Padmalochana and Rajan, 2015;Shalaby and Hammouda, 2014;Tavafi et al, 2012). Tecoma stans leaves, bark and roots contain many biologically active chemicals and extracts from those tissues have been used in traditional folk medicine to treat many diseases and conditions (Liogier, 1990).…”
Section: Introductionsupporting
confidence: 80%
“…frecuentemente en el tratamiento de infecciones producidas por bacterias aerobias gram negativas; sin embargo, su terapia está relacionada con una de las complicaciones más frecuentes, la nefrotoxicidad 1,2,3,4 . Las concentraciones elevadas de esta droga en la superficie del endotelio capilar glomerular y del epitelio tubular renal producen aumento de los niveles de creatinina sérica, alteraciones morfológicas como edema y necrosis a nivel tubular, todo esto produce un aumento del estrés oxidativo y toxicidad renal 2 .…”
unclassified
“…Las concentraciones elevadas de esta droga en la superficie del endotelio capilar glomerular y del epitelio tubular renal producen aumento de los niveles de creatinina sérica, alteraciones morfológicas como edema y necrosis a nivel tubular, todo esto produce un aumento del estrés oxidativo y toxicidad renal 2 . Estudios previos han demostrado que el efecto nefrotóxico de la gentamicina puede ser mediado por la sobreproducción de especies reactivas de oxigeno (EROS), y esto debido a un incremento significativo de hidroperóxidos lipídicos y radicales hidroxilos, lo que ocasiona lesión a nivel de las estructuras internas de la nefrona 3,4,5,6,7 .…”
unclassified
See 1 more Smart Citation
“…[3] The mechanism of gentamicin-induced nephrotoxicity in rats is through generation of oxidative stress which is mainly due to the production of reactive oxygen species (ROS) such as superoxide anions, hydroxyl radicals, and hydrogen peroxide and inhibition of oxidative phosphorylation. [4,5] ROS may result in the development of oxidative stress that may cause kidney damage. [6] Various inflammatory mediators responsible for inflammation may also result…”
mentioning
confidence: 99%